Secreted Isoform of Human Lynx1 (SLURP-2): Spatial Structure and Pharmacology of Interactions with Different Types of Acetylcholine Receptors - Lyukmanova, E N; Shulepko, M A; Shenkarev, Z O; Bychkov, M L; Paramonov, A S; Chugunov, A O; Kulbatskii, D S; Arvaniti, M; Dolejsi, Eva; Schaer, T; Arseniev, A S; Efremov, R G; et al. (Scientific reports, 2016)
Human-secreted Ly-6/uPAR-related protein-2 (SLURP-2) regulates the growth and differentiation of epithelial cells. Previously, the auto/paracrine activity of SLURP-2 was considered to be mediated via its interaction with the α3β2 subtype of the nicotinic acetylcholine receptors (nAChRs). Here, we describe the structure and pharmacology of a recombinant analogue of SLURP-2. Nuclear magnetic resonance spectroscopy revealed a 'three-finger' fold of SLURP-2 with a conserved β-structural core and three protruding loops. Affinity purification using cortical extracts revealed that SLURP-2 could interact with the α3, α4, α5, α7, β2, and β4 nAChR subunits, revealing its broader pharmacological profile. SLURP-2 inhibits acetylcholine-evoked currents at α4β2 and α3β2-nAChRs (IC50 ~0.17 and >3 μM, respectively) expressed in Xenopus oocytes. In contrast, at α7-nAChRs, SLURP-2 significantly enhances acetylcholine-evoked currents at concentrations <1 μM but induces inhibition at higher concentrations. SLURP-2 allosterically interacts with human M1 and M3 muscarinic acetylcholine receptors (mAChRs) that are overexpressed in CHO cells. SLURP-2 was found to promote the proliferation of human oral keratinocytes via interactions with α3β2-nAChRs, while it inhibited cell growth via α7-nAChRs. SLURP-2/mAChRs interactions are also probably involved in the control of keratinocyte growth. Computer modeling revealed possible SLURP-2 binding to the 'classical' orthosteric agonist/antagonist binding sites at α7 and α3β2-nAChRs.
Keywords: CHO buňky; Humans; PC12 Cells; evokované potenciály; lidé středního věku; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; Protein Binding; epilepsie temporálního laloku; buňky PC12; Computer Simulation; Keratinocytes; nikotinové receptory; Female; adaptorové proteiny signální transdukční; dospělí; keratinocyty; Receptors, Nicotinic; krysa rodu Rattus; alpha7 Nicotinic Acetylcholine Receptor; vazebná místa; lidé; receptory muskarinové; zvířata; proliferace buněk; Xenopus; Adaptor Proteins, Signal Transducing; GPI-Linked Proteins; Binding Sites; CHO Cells; oocyty; Cricetulus; buněčné linie; Adult; počítačová simulace; ženské pohlaví; Cell Line; Evoked Potentials; Middle Aged; Cell Proliferation; vazba proteinů; Epilepsy, Temporal Lobe; alfa7 nikotinové acetylcholinové receptory; Rats; Receptors, Muscarinic; Animals; GPI-vázané proteiny; Oocytes